2013
DOI: 10.1371/journal.pone.0066698
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Post-Discharge Mortality in Resource Poor Countries: A Systematic Review

Abstract: ObjectivesMortality following hospital discharge is an important and under-recognized contributor to overall child mortality in developing countries. The primary objective of this systematic review was to identify all studies reporting post-discharge mortality in children, estimate likelihood of death, and determine the most important risk factors for death.Search StrategyMEDLINE and EMBASE were systematically searched using MeSH terms and keywords from the inception date to October, 2012. Key word searches us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
130
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(135 citation statements)
references
References 18 publications
5
130
0
Order By: Relevance
“…Post-discharge deaths generally occurred early (within several weeks of discharge) and in many cases did not occur in hospitals. 4 A recent systematic analysis of severe acute respiratory infections (ARIs) in children under 5 years found that although most episodes (62%) were treated in the hospital, 81% of the deaths from severe respiratory infection occurred outside of the hospital. 2 This study did not identify the proportion of out of hospital deaths which at some point received hospital care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-discharge deaths generally occurred early (within several weeks of discharge) and in many cases did not occur in hospitals. 4 A recent systematic analysis of severe acute respiratory infections (ARIs) in children under 5 years found that although most episodes (62%) were treated in the hospital, 81% of the deaths from severe respiratory infection occurred outside of the hospital. 2 This study did not identify the proportion of out of hospital deaths which at some point received hospital care.…”
Section: Introductionmentioning
confidence: 99%
“…7 Malnutrition, previous hospitalizations and HIV are often identified as key risk factors for post-discharge mortality. 4 While these risk factors may assist clinicians in the identification of vulnerable children, many other contextual and social factors may contribute to post-discharge mortality. Currently, little is known about the health seeking decisions made by caregivers following hospitalizations for acute illness.…”
Section: Introductionmentioning
confidence: 99%
“…The median age of these children was 6 months, and according to the authors, were suspected to have suffered a relapse of pneumonia. The most important variables associated with post-discharge mortality were determined to be young age and malnutrition according to a multivariate analysis [30]. Severe anemia specifically has been predicted to account for higher post-hospital discharge mortality in children [15].…”
Section: Study Population Standard Of Care In Hicmentioning
confidence: 99%
“…A recent systematic review has found that the months following hospital discharge account for at least as many deaths as the hospital period. 4 Despite the apparently high burden of post discharge mortality in children, little currently exists to address this important issue. The identification of vulnerable children is an important first step in addressing this important public health problem.…”
Section: Introductionmentioning
confidence: 99%